Prevalence and Associated Factors of Postpartum Depression among Women in Central Region of Saudi Arabia - Huda Hakim Abd Elrahman, Alanoud Muteb Alshammar, Nourah Mohammed Alotaibi, Mariam Awwad Al-Mutairi, Munira Mohammed Alhaidari, Ghadi Ali Alfadhil, Saira Farhan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Postpartum depression is one of the most common psychological problems in women worldwide. Globally, it was estimated that 10% of women have a mental illness, mainly depression, during pregnancy, whereas 13% after giving birth. This study aims to identify the prevalence and associated factors of postpartum depression among married women in the central region of Saudi Arabia. Material and Methods: A community-based cross-sectional study was conducted from October 2020 to June 2021 in Ar-Riyadh province, located in the center part of the country. The information in this study was collected using online web media, which incorporated Edinburgh postnatal depression scale to assess postpartum depression. This study followed a simple random sampling method where the sample was selected based on the response that meets the required age group and has at least one pregnancy experience in their lifetime. A total of 1067 sample was taken for the study, among which 907 were reached. The collected information was entered and analyzed using SPSS version 21, where the required analysis was performed to present the information. Results: In this study, among 907 respondents, most (34%) of the respondents were from the age group 31-40, and the majority of them were married, 90%. Likewise, Two-third of the respondent (66.6%) reported that they got a lot of social support from the child's father, while one-third (33.4%) did not receive much support. The study also indicated that more than 50% reported being on postpartum depression and that which majority of respondents (92.6%) did not have a history of depression. In comparison, 7.4% reported a history of depression. Here, a significant association was seen between the number of children and PPD (P=<0.001). Also, a significant association was seen between mothers' history of depression and the occurrence of postpartum depression (P=<0.001). Conclusion: The study concluded that there is a high prevalence of PPD among women in the Central region of Saudi Arabia, which is an alarming issue. Therefore, there is an increased need of often screening and preventive treatment as the support for managing the mental issues of the mothers.